2007
DOI: 10.1016/j.expneurol.2007.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Non-steroidal anti-inflammatory drugs in Parkinson's disease

Abstract: Parkinson's disease (PD) is known to be a chronic and progressive neurodegenerative disease caused by a selective degeneration of dopaminergic (DAergic) neurons in the substantia nigra pars compacta (SNc). A large body of experimental evidence indicates that the factors involved in the pathogenesis of this disease are several, occurring inside and outside the DAergic neuron. Recently, the role of the neuron-glia interaction and the inflammatory process, in particular, has been the object of intense study by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
181
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(185 citation statements)
references
References 189 publications
(250 reference statements)
3
181
1
Order By: Relevance
“…46 In addition, the frequency of various HLA antigens was increased in patients with PD and in patients dying from postencephalitic PD. [53][54][55] Although PD is clearly not an autoimmune disorder, the occurrence of a localized attack of microglia during the disease course has been demonstrated with epidemiological, 56,57 animal model 58,59 and cell culture [60][61][62] approaches. Zhang et al 63 reported that aggregated a-synuclein activates microglia which, as a consequence, are toxic toward cultured dopaminergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…46 In addition, the frequency of various HLA antigens was increased in patients with PD and in patients dying from postencephalitic PD. [53][54][55] Although PD is clearly not an autoimmune disorder, the occurrence of a localized attack of microglia during the disease course has been demonstrated with epidemiological, 56,57 animal model 58,59 and cell culture [60][61][62] approaches. Zhang et al 63 reported that aggregated a-synuclein activates microglia which, as a consequence, are toxic toward cultured dopaminergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that inflammation may be related to the pathogenesis of PD has been derived from postmortem studies showing the presence of activated microglia cells and increased levels of inflammatory cytokines in substantia nigra and striatum [548][549][550][551]. A few studies also reported altered levels of serum inflammatory markers in PD patients [552][553][554].…”
Section: Inflammationmentioning
confidence: 99%
“…Non-steroidal anti-inflammatory drugs (NSAIDs) protected against neuronal loss caused by MPTP in animals [551]. Based on this evidence, epidemiological studies have investigated the possible role of NSAIDs in PD.…”
Section: Inflammationmentioning
confidence: 99%
“…Therefore, the inhibition of microglial activation could reduce neuronal cell death. In fact, a number of anti-inflammatory agents, which inhibit microglial activation or production of proinflammatory mediators under the central nervous system disease conditions, attenuate neuronal degeneration (35,36).…”
Section: Discussionmentioning
confidence: 99%